Solve all your doubts with Teachoo Black (new monthly pack available now!)

Ex 4.5

Ex 4.5, 1

Ex 4.5, 2

Ex 4.5, 3 Important

Ex 4.5, 4 Important

Ex 4.5, 5

Ex 4.5, 6 Important

Ex 4.5, 7

Ex 4.5, 8

Ex 4.5, 9

Ex 4.5, 10 Important

Ex 4.5, 11 Important You are here

Ex 4.5, 12

Ex 4.5, 13

Ex 4.5, 14 Important

Ex 4.5, 15 Important

Ex 4.5, 16

Ex 4.5, 17 (MCQ) Important

Ex 4.5, 18 (MCQ) Important

Chapter 4 Class 12 Determinants

Serial order wise

Last updated at Jan. 22, 2020 by Teachoo

Ex 4.5, 11 Find the inverse of each of the matrices [■8(1&0&0@0&cos𝛼&sin𝛼@0&sin𝛼&−cos𝛼 )] Let A =[■8(1&0&0@0&cos𝛼&sin𝛼@0&sin𝛼&−cos𝛼 )] We know that A–1 = 1/(|A|) (adj A) exists if |A|≠ 0 Calculating |A| |A| = |■8(1&0&0@0&cos𝛼&sin𝛼@0&sin𝛼&−cos𝛼 )| = 1 |■8(cos𝛼&sin𝛼@sin𝛼&−cos𝛼 )|– 0 |■8(0&sin𝛼@0&〖− cos〗𝛼 )|+ 0|■8(0&cos𝛼@0&𝑠𝑖𝑛 𝛼)| = 1(– cos2α – sin2α ) – 0 + 0 = –( cos2α + sin2α ) = –1 Since |𝐴|≠ 0 Thus A-1 exists Calculating adj A adj (A) = [■8(A11&A21&A31@A12&A22&A32@A13&A23&A33)] A = [■8(1&0&0@0&cos𝛼&sin𝛼@0&sin𝛼&−cos𝛼 )] M11 = |■8(cos"α" &sin"α" @sin"α" &−cos"α" )| = –cos2α – sin2α = –(cos^2α 〖+ 𝑠𝑖𝑛〗^2α ) = –1 M12 = |■8(0&sin 𝛼@0&−cos 𝛼)| = 0 – 0 = 0 M13 = |■8(0&cos𝛼@0&sin 𝛼)| = 0 – 0 = 0 M21 = |■8(0&0@sin 𝛼&−cos𝛼 )| = 0 – 0 = 0 M22 = |■8(1&0@0&−cos 𝛼)| = –cos α – 0 = –cos α M23 = |■8(1&0@0&sin𝛼 )| = sin α = 0 = sin α M31 = |■8(0&0@cos 𝛼&sin 𝛼)| = 0 – 0 = –0 M32 = |■8(1&0@0&sin 𝛼)| = sin α – 0 = sin α M33 = |■8(1&0@0&cos 𝛼)| = cos α + 0 = cos α Now, A11 = 〖(−1)〗^(1+1) M11 = 〖(−1)〗^2 (–1)2 = –1 A12 = 〖(−1)〗^(1+2) M12 = 〖(−1)〗^3 0 = 0 A13 = 〖(−1)〗^(1+3) M13 = 〖(−1)〗^4 0 = 0 A21 = 〖(−1)〗^(2+1)M21 = (–1)3 0 = 0 A22 = 〖(−1)〗^(2+2) M22 = 〖(−1)〗^4(– cos α) = –cos α A23 = 〖"(– 1)" 〗^(2+3) M23 = 〖"(–1)" 〗^5 sin α = –sin α A31 = 〖(−1)〗^(3+1). M31 = 〖(−1)〗^4 0 = 0 A32 = 〖(−1)〗^(3+2)sin α = (–1)5 sin α = –sin α A33 = 〖(−1)〗^(3+3)M33 = (–1)6 cos α = cos α So, adj (A) = [■8(A11&A21&A31@A12&A22&A32@A33&A23&A33)] = [■8(−1&0&0@0&−cos𝛼&−sin𝛼@0&−sin𝛼&cos𝛼 )] Calculating inverse Now, A– 1 = 1/(|A|) ( adj (A)) = 1/(−1) [■8(−1&0&0@0&−cos𝛼&−sin𝛼@0&−sin𝛼&cos𝛼 )] = – [■8(−1&0&0@0&−cos𝛼&−sin𝛼@0&−sin𝛼&cos𝛼 )] = [■8(𝟏&𝟎&𝟎@𝟎&𝒄𝒐𝒔𝜶&𝒔𝒊𝒏𝜶@𝟎&𝒔𝒊𝒏𝜶&〖−𝒄𝒐𝒔〗𝜶 )]